Novel High Spatiotemporal Resolution Versus Standard-of-Care Dynamic Contrast-Enhanced Breast MRI: Comparison of Image Quality - Morrison, Courtney K. (Invest Radiol, 2017)
OBJECTIVE: Currently, dynamic contrast-enhanced breast MRI prioritizes spatial resolution over temporal resolution given the limitations of acquisition techniques. The purpose of our intra-patient study was to assess the ability of a novel high spatial and high temporal resolution DCE breast MRI method to maintain image quality compared to the clinical standard-of-care (SOC) MRI. MATERIALS AND METHODS: Thirty patients, each demonstrating a focal area of enhancement (29 benign, 1 cancer) on their SOC MRI consented to undergo a research DCE breast MRI on a second date. For the research DCE MRI, a method (DISCO) employing pseudo-random k-space sampling, view sharing reconstruction, two-point Dixon fat-water separation, and parallel imaging was used to produce images with an effective temporal resolution six times faster than the SOC MRI (27 seconds versus 168 seconds, respectively). Both the SOC and DISCO MR images were acquired with matching spatial resolutions of 0.8 × 0.8 × 1.6 mm(3). Image quality (distortion/artifacts, resolution, fat suppression, lesion conspicuity, perceived SNR, and overall image quality) was scored by three radiologists in a blinded reader study. RESULTS: Differences in image quality scores between the DISCO and SOC images were all less than 0.8 on a 10-point scale, and both methods were assessed as providing diagnostic image quality in all cases. DISCO images with the same high spatial resolution, but six times the effective temporal resolution as the SOC MR images were produced, yielding 20 post-contrast time-points with DISCO compared with three for the SOC MRI, over the same total time interval. CONCLUSIONS: DISCO provided comparable image quality compared to the SOC MRI, while also providing six-times faster effective temporal resolution and the same high spatial resolution.